COMPARISONS OF ESTUARINE MANAGEMENT NEEDS OF A TROPICAL PACIFIC MEXICAN HARBOUR AND A TEMPERATE CALIFORNIA HARBOUR - Soule, Dorothy F.; Morris, Penny A.; Soule, John D. (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 1977)
Two areas of the eastern Pacific are compared, the southern California wetlands south of Point Conception and Mazatlan, Mexico. The historical development of both areas is important in considering their present biological status. Southern California has been subjected to intensive population growth and urbanization while Mazatlan has remained relatively unchanged. Both areas are compared biologically in regards to the fish population, thermal gradients in the harbors, salinity, nitrate, nitrite and phosphate distributions. The economic importance of the harbors is recognized, however it is essential that measures are taken to restore or retain existing wetlands that are associated with the harbors. The harbors can serve as shelters for various organisms if water quality can either be maintained (as in the case of Mazatlan) or improved, and if input of toxic and excessive nutrients is limited.